ETHNOCULTURAL TOURISM - THE EXPERIENCE OF THE MOST DEVELOPED COUNTRIES - Kilichova Orzigul Zafar qizi (Modern American Journals, 2025)
This article analyzes the countries of Africa, Europe and Asia, where ethnocultural tourism is more developed, and also discusses ways to effectively use the material and intangible resources of ethnocultural tourism in our country. In conclusion, it is proposed to encourage ethnocultural tourism in combination with other types of tourism, including gastronomic tourism, as well as to create ethnocultural tourist landscapes.
Keywords: tourism, ethnography, culture, economics, ethnographic tourism, intangible heritage, resource, experience, factors.